Linkage between the leader sequence and leader RNA production in Borna disease virus-infected cells - Honda, Tomoyuki; Sofuku, Kozue; Kojima, Shohei; Yamamoto, Yusuke; Ohtaki, Naohiro; Tomonaga, Keizo (Virology (New York, N.Y.), 2017)
The 3′-untranslated region (UTR) of the non-segmented, negative-strand (NNS) RNA viral genome is called the leader sequence, and functions as the promoter for viral replication and transcription. NNS RNA viruses also use the sequence as a template to synthesize leader RNAs (leRNAs) with unknown functions. Borna disease virus (BDV) is unique because it establishes a persistent infection and replicates in the nucleus. No report has yet demonstrated the presence of leRNAs during BDV infection. Here, we report that BDV synthesizes leRNAs from the 3′-UTR of the genome. They started at position 5 in the 3′-UTR and ended by the transcription start signal of the nucleoprotein gene. The level of leRNA production is not correlated with the levels of viral replication and transcription. On the other hand, mutation of the 3′-UTR affects leRNA production. Our findings add a novel viral transcript to the BDV life cycle and shed light on BDV replication and/or transcription. •BDV produces leRNAs using the 3′-UTR of the genome as a template.•Level of BDV leRNA production is not correlated with viral replication and/or transcription.•A mutation at position 30 in the 3′-UTR affects BDV leRNA biogenesis.